O ato criador como práxis arte-educativa na formação de professores de artes visuais - Silva, Maria Cristina da Rosa Fonseca e (2019)
We investigated an experimental, dialogical process, such as the formation of teachers of Visual Arts in contemporary times, based on Materialism-historical and dialectical. Mediation as artistic and art / educational praxis are conceived as a creative process, in a process shared by the creative act, through theoreticalpractical workshops, in the characteristic of the specificity of art